Can culture confirmation of gonococcal infection be improved in female subjects found to be positive by nucleic acid amplification tests in community clinics?. Issue 7 (24th August 2009) - Rao, G Gopal; Bacon, L; Evans, J; Dejahang, Y; Hardwick, R; Michalczyk, P; Wong, J; Donaldson, A
Abstract : Background: Use of nucleic acid amplification tests (NAATs), such as strand displacement assay (SDA, BD ProbeTec C trachomatis/N gonorrhoeae Amplified DNA Assay), for the detection of gonococcal infection in the community is controversial because of the possibility of false-positive results in low prevalence populations. Aim: To evaluate if culture confirmation of gonococcal infection can be improved for subjects found to be positive by BD ProbeTec in community clinics. Methods: Two cervical swabs were collected for culture to confirm NAAT positive results in women aged over 16 years—a majority of whom were <25 years and asymptomatic. One swab was urgently transported (UTP) and processed in the laboratory within 2 hours whereas the other swab (RTP) was stored at 4°C, transported at room temperature and processed 4–72 hours after collection depending on the time and day of collection. Results: Altogether, 56 subjects with NAAT positive results were recruited into the study. Nine (16.1%) subjects who were culture negative were excluded from final analysis due to prior antibiotic treatment (4/9) or the culture having been taken more than 1 month after the NAAT was positive (4/9) or an incorrect specimen being received (1/9). Overall, 41/47 (87.2%) NAAT positive subjects were confirmed by culture. In total, 40/47 (85.1%) UTP swabs and 27/47 (57.4%) RTP swabs were positive (p<0.05). Conclusion: This study shows that culture confirmation in NAAT positive subjects in a community gonococcus screening programme can be significantly improved by urgent transportation to and processing of specimens in the laboratory.